Peran Humas dalam Mencegah Kasus Pelecehan Seksual di Perguruan Tinggi Bangka Belitung - Putri, Sekar; Yulista, Yera (Program Study of Islamic Communication and Broadcasting, Faculty of Da’wa and Islamic Communication, State Institute for Islamic Studies of Syaikh Abdurrahman Siddik Bangka Belitung, 2025)
This study aims to analyze the role of public relations (PR) in several higher education institutions in Bangka Belitung, using Dozier and Broom’s public relations role theory as the main framework. The research focuses on how PR functions in the prevention and handling of sexual harassment cases, as well as its role in maintaining institutional image and crisis communication. The findings reveal a diverse spectrum of PR roles across institutions. Atma Luhur University and other institutions without formal PR units still limit PR functions to communication technician and communication facilitator. STIKES Citra Delima and STIE IBEK demonstrate more advanced roles, yet remain confined to technical and facilitation aspects without strategic involvement. STIE Pertiba exhibits a stronger role, functioning as both problem solving facilitator and expert prescriber in handling sexual harassment cases. Meanwhile, Polman Negeri Bangka Belitung represents the most comprehensive model, where PR performs across all role spectrums from technical tasks and facilitation to problem solving and strategic policy advising. This study concludes that the effectiveness of PR roles in higher education is strongly influenced by institutional structure, policy frameworks, and the recognition of PR as a strategic actor by university leadership.